Dinamika Pengisian Jabatan Presiden dan Pemberhentian Presiden dan Wakil Presiden di Indonesia - Sulardi, Sulardi (Unisia, 2016)
Power and authority of executive Institute experience dynamics lead to executive institute which its reside in at system governance of presidential. Lying between election of vice president and president by people, domiciling president as governance head and president, and also mechanism cessation of president. This condition indicates that still, needed by make-up of system principles governance of presidential, so that management of govemance can walk effectively and is efficient. Each state institute has to equivalent domicile and have different authority, but remain to stay in corridor check and balance. Election dynamics of president republic of Indonesia is since Indonesia of independence to be conducted different in the way of and unequal legal fundament. Mechanism, election of president in Indonesia is first time conducted by state bodies (PPKI, MPRS, MPR). Legal consequences (which have been specified in law), and selected direct by people. Lifting of direct selected president by people early at 1999 up to 2001, since happened alteration of the constitution 1945. One of them with related to election of president, from election of president by MPR become president selected directly by people base onsection 6A sentence (1). Election of vice president and president directly create counter balance between various strength in management of state especially in creating check and balance, among president with delegation institute because both of the same selected by people. While for the cessation of previous president represent political mechanism. To arrest president, DPR is enough by proposing to MPR so that performing a special conference to arrest president. After alteration of the constitution 1945-mechanism cessation of president entangle state institute besides DPR and MPR, that is MK (constitution court), passing conference process just open and fair, ifinitially president can be arrested by because reason of collision of state having the character of politics and multi interpretation, hence in this time affirmed that president and/orvice president can only be arrested by because just legal ground, that is: heavy transgression, conducting culpable deed, experiencing of change so that no longer eligible as president and/orvice president. Cessation mechanism like this referred as with impeachment. Impeachment goes into effect special for president and/or vice president with term "can be arrested in a period of its position”. Attendance of this section is become counterbalance of reinforcement of system of presidential post constitution amendment.